AKIBAT HUKUM PENJATUHAN PUTUSAN VERSTEK DALAM SENGKETA WARIS - Rizki Nurdiansyah; Muhamad Romdoni; Santy Fitnawati WN (Yurisprudentia: Jurnal Hukum Ekonomi, 2022)
This study examines the inheritance dispute submitted to the Serang Religious Court by the Plaintiffs with case register No. 0551/Pdt.G/2021/PA.Srg but not attended by the Defendants. This study aimed to examine the process of resolving inheritance disputes that were not attended by the Defendants and to analyze the legal consequences of the versek decision by the panel of judges. This study uses a normative juridical method with a law approach and a case approach. The data used are secondary, consisting of primary, secondary, and tertiary legal materials. The data obtained are then inventoried and identified, managed, and analyzed qualitatively using deductive logic thinking. The results of this study indicate that inheritance disputes not attended by the Defendants can still be carried out under procedural law with a verstek decision. The legal consequences of the verstek have implications for the defendants who must accept the verdict from the Serang Religious Court judges. However, if they do not accept the decision, the Defendants can still file a legal action, namely verzet.